Manajemen Kelembagaan dan Akademik Lembaga Pendidikan Maarif Nahdlatul Ulama Kota Samarinda Kalimantan Timur - AR, Abdurrahman (SYAMIL, 2017)
TheEducational Management and Academic Of Maâarif Nahdlatul Ulama in Samarinda, East Kalimantan, is to coming up a moeslem organization in the educational prospective and progressive mutual organization and education to come up image of Nahdlatul Ulama as theÂ  biggest moeslem organization in Indonesia.The objective of this research was to identificate the Educational management and Academic quality and to doctrine the religious values to the basic Maâarif Nahdlatul UlamaInstitute in Samarinda, East Kalimantan. This research also designed to get the object datas from the three Islamic Elementry schools which organized by Maâarif Nahdlatul Ulama Samarinda through many kind ways they are; (1) Interviews Elementry head masters and their commitees, (2) pictures, (3) schoolâs data or documents.The purpose of data collection wantsÂ  to understand the Moslem Elementry School of Maâarif Nahdlatul Ulama conditions in the some areas in Samarinda in orderÂ  to know what are the weakness and lack of Maâarif NU. The result of dataanalysis indicated three of Moslem Elementry School Maâarif NU thoselocated in Samarinda city, they are MI 01 in Palaran, MI.02 Sindang Sari, MI 03 Jln. Rukun Samarinda Seberang, they still run in slowly.The researcherâs summary in this research those, from three of Madrasah Ibtidaiyyah of Educational Institute Maâarif NU still need high supports from everyone, from moeslem who love education progressive now and the future.